Hubungan Komunikasi Terapeutik yang Diberikan Perawat Terhadap Kecemasan Keluarga Pasien di ICU RSUD Meuraxa Kota Banda Aceh - Rifa Almudhia; Urip Pratama; Iskandar Iskandar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Anxiety among family member in the Intensive Care Unit (ICU) is a common psychological issue. This situation arises from the uncertainty about the patient’s condition. Effective therapeutic communication by nurses is one of the key strategies to help reduce anxiety. This study was conducted from June 4 to July 20, 2025. This study aims to analyze the relationship between nurses’ therapeutic communication and the anxiety levels of family members in the ICU of RSUD Meuraxa, Banda Aceh. This research employed a quantitative, correlational design. The population consisted of 66 family members of ICU patients, with a sample of 57 respondents selected using a purposive sampling technique. The results showed that most families received therapeutic communication at a moderate level (50.9%) and a good level (49.1%). The anxiety levels experienced by the families were mostly moderate (54.4%) and mild (45.6%). The analysis revealed a p-value of 0.003, indicating a statistically significant relationship between nurses’ therapeutic communication and the anxiety levels of family member. These findings prove that therapeutic communication given by nurses plays a vital role in influencing the anxiety levels of patients’ families in the ICU. Therefore, the hospital management is encouraged to improve nurses’ therapeutic communication skills and establish supportive communication policies to enhance services and reduce anxiety among the family members in the ICU.